Second-generation BRAF inhibitor Encorafenib resistance is regulated by NCOA4-mediated iron trafficking in the drug-resistant malignant melanoma cells - Ceyda Colakoglu Bergel; Isil Ezgi Eryilmaz; Gulsah Cecener; Unal Egeli (Scientific Reports)
Abstract The current study established the first in vitro Encorafenib resistance protocol in BRAF-mutated malignant melanoma (MM) cells and investigated the resistance-related mechanisms. After establishing Encorafenib-resistant A375-MM cells, resistant-related mechanisms were investigated using WST-1, Annexin V, cell cycle, morphological analysis, live-cell, Western blot, RNA-Seq, transmission electron microscopy-(TEM), oxidative stress and iron colorimetric assay. The most resistant group, called A375-R, was determined in the cells treated with a constant dose of 10 nM over 3 months. The viability, apoptosis, and G0/G1 arrest reflected the acquired chemoresistance. Autophagic Beclin and LC3 proteins, and AKT signaling increased in the A375-R. RNA-Seq results also exhibited altered epigenetic regulation of resistance; particularly ferritin family members, ion transport pathways. Then, increased NCOA4, FTH1, and iron levels detected in A375-R suggest that the iron metabolism-related mechanism, such as ferritinophagy, might be triggered, which was supported by TEM and oxidative stress analysis. Iron storage, transport, and ferritinophagy have the promising potential to be targeted for combining with BRAF-targeted therapy to reverse Encorafenib resistance in MM. Moreover, this is the first study evaluating in vitro Encorafenib resistance mechanisms, and we suggest that our findings contribute to improving new drug combinations targeting BRAF and iron metabolism in different MM cells.